Association between Adherence to a Mediterranean Diet Pattern and DNA Methylation of the Main Autophagy-Related Genes. (14th June 2022) - Corella, Dolores; Fernández-Carrión, Rebeca; Portolés, Olga; Francés, Francesc; Saiz, Carmen; Barragán, Rocío; Castelló-Ponce, Ana; Guillem-Saiz, Patricia; Coltell, Oscar; Sorlí, Jose
Abstract: Objectives: Autophagy is a dynamic process responsible for protein degradation/recycling as a protective mechanism in response to stress and inflammation. Its deregulation has been associated with common cv and brain diseases. In animal models, autophagy activity is regulated by epigenetic mechanisms in response to diet. However, very few studies have analyzed the diet-autophagy relationship in humans. Our aim is to study the association between the adherence to the Mediterranean diet (MedDiet) and the DNA-methylation of the main autophagy-related genes. Methods: We have analyzed 410 subjects (aged 65.5 y) with metabolic syndrome from Valencia (Spain) and measured the adherence to the MedDiet by a 17-item score. DNA methylation from leukocytes was analyzed by the Illumina EPIC850K Human array. A comprehensive list (n = 141) of the main autophagy-related genes was selected from the literature. Multivariate adjusted models including potential confounders were fitted and gene-ontology (GO) enrichment was analyzed. Results: In a model adjusted for sex, age, batch effect, diabetes, body mass index, medications, leukocyte types, smoking and adherence to MedDiet, we found significant associations between MedDiet adherence and the differential methylation of several cpg sites of the selected autophagy-related genes: cg17676428 (top-ranked cpg site) in TOLLIP (Toll interactive protein) gene (p = 9.3 × 10–6). This is a ubiquitin binding protein that regulates innate immune response. Its deficiency alters atherosclerosis and steatosis. The other hits: cg12573747 in HTT (Huntingtin) gene (p = 4.5 × 10–5), a gene related to the DNA protection in neurons; the cg09197074 (p = 7.8 × 10–5) in HSPA8 (Heat shock protein family A (Hsp70) member 8), that functions as a chaperone and protects the proteome from stress. The GO analysis identified as top-ranked enriched functions: autophagosome membrane; organelle disassembly; selective autophagy; vacuole; phagophore assembly; etc. Conclusions: A higher adherence to the MedDiet is associated with differential DNA-methylation on relevant autophagy related genes and may have a potential effect upregulating autophagy. Funding Sources: Generalitat Valenciana (grant PROMETEO/2021/021). Grant PID2019-108858RB-I00 is funded by AEI 10.13039/501100011033 and, by "ERDF A way of making Europe".